Pilea victoriae (Urticaceae): a new record for the Flora of Nepal - Chalise , P.; Dhakal , S.; Paneru, Y. R. (Rheedea, 2025)
Pilea victoriae V.Suresh & Sojan (Urticaceae) is reported here as a new addition to the flora of Nepal. The species has been documented from multiple localities across eastern and central Nepal. Pilea victoriae can be distinguished from its allied Nepalese species, P. microphylla, by its erect stems, petiole length, leaves and flowers characteristics. A brief description, diagnostic key, photographs and distribution are provided in this article.